2022
DOI: 10.3390/healthcare10091766
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Benefits of Exercise: Is There a Time-of-Day Effect?

Abstract: It is well established that physical activity benefits cognition. Further, the time of day one engages in physical activity has been suggested to influence cognition. Here, we aimed to understand if there is a time-of-day effect (morning or afternoon) of physical activity on cognition, i.e., if exercising in the morning or afternoon might bring greater cognitive benefits. A total of 56 participants were allocated to one of two groups with the same baseline cognitive performance as well as fitness level (Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…To assess the presence of cognitive impairment that might compromise participation, we used the Mini-Mental State Examination (MMSE) cut-off point ≥19 (Yeh et al, 2021) before acute (T0) and after 12-week chronic exercise (T2). Attention and concentration performance was assessed at baseline (T0), post-acute (T1) and post-chronic intervention (T2) using the d2 Test of Attention (Brickenkamp, 2007;Maeneja et al, 2022).…”
Section: Interventionmentioning
confidence: 99%
See 4 more Smart Citations
“…To assess the presence of cognitive impairment that might compromise participation, we used the Mini-Mental State Examination (MMSE) cut-off point ≥19 (Yeh et al, 2021) before acute (T0) and after 12-week chronic exercise (T2). Attention and concentration performance was assessed at baseline (T0), post-acute (T1) and post-chronic intervention (T2) using the d2 Test of Attention (Brickenkamp, 2007;Maeneja et al, 2022).…”
Section: Interventionmentioning
confidence: 99%
“…To assess participants' perceived difficulty after 5 min of recovery from the task, a Visual Analog Scale (VAS) (Maeneja et al, 2022), was applied after the d2 Test of Attention. To assess participants' perceived exertion, the Borg Perceived Effort Rating Scale (Borg, 1982;Aamot et al, 2014) was applied after the acute and last training session of each week throughout the 12-week chronic intervention protocol (Borg, 1982;Maeneja et al, 2022), as shown in Figure 1.…”
Section: Interventionmentioning
confidence: 99%
See 3 more Smart Citations